Implementasi Pendidikan Karakter Melalui Kegiatan Ekstrakurikuler Panahan - Ula Nur Azizah; Saeful Anwar; Ase Kurniawan (THORIQOTUNA: Jurnal Pendidikan Islam, 2024)
The deviation of character values ​​that often occurs in the digital era like today is making its users more apathetic and individualistic. Character education is education that prioritizes the essence and meaning of morals and ethics, so that it will be able to form good students' personalities. This study aims to analyze and explain the implementation of Character Education through extracurricular activities at SMKIT Abu Dzar. This study is qualitative and takes interview, observation and documentation data. The results of this study are that the implementation of the archery extracurricular program at SMKIT Abu Dzar is one of the extracurricular activities for students that aims to strengthen the character of students through structured activities. This archery program has succeeded in instilling character values ​​such as spirituality, discipline, hard work, independence, appreciation for achievement, and friendly/communicative attitudes. This character is reflected in the daily habits of students at school, which develop through repeated practice so that it becomes part of their lives and the instilled character values ​​have a positive impact on students.